Narrative analysis of 'skandal mahkamah keluarga' in Tempo magazine, October 2023 - Salman Alfarisi; Fingky Ayu Puspitasari (Jurnal Studi Komunikasi, 2024)
This research involves a narrative analysis of the news text published in the October 22, 2023, edition of Tempo magazine titled 'Skandal Mahkamah Konstitusi' The Constitutional Court granted the age requirement for presidential and vice-presidential candidates, stipulating that they must be at least 40 years old or have experience as a regional head. As the 2024 Presidential General Election drew nearer, the case became highly controversial. This research explores how Tempo framed its narrative in reporting the Constitutional Court Lawsuit, utilising the Algirdas Greimas model for narrative analysis. The study is qualitative and descriptive. The discussion results reveal that in that edition, Tempo, specifically reported the involvement of Anwar Usman, the Chairman of the Constitutional Court. Anwar Usman was portrayed as the party attempting to navigate the lawsuit with various news narratives, such as 'manoeuvring' and 'lobbying,' during the trial process. Tempo aimed to convey the message that the decision raised various complicated issues and reflected the complex dynamics within the Constitutional Court. Tempo, as a news source, plays a critical role in uncovering hidden realities that can only be revealed through in-depth investigation and extracting information from internal sources within the Constitutional Court. This is Tempo's main strength.